Hyponatremia due to Severe Primary Hypothyroidism in an Infant - Agathis, Nickolas T.; Libman, Ingrid M.; Moritz, Michael L. (Frontiers in Pediatrics, 2015)
Hyponatremia has been reported in the elderly with hypothyroidism and myxedema, but this has not been a universal finding in clinical studies and there have been only a few reports in children. We report a case of an infant who developed hyponatremia due to severe primary hypothyroidism. A 4-month-old ex-preterm male, who had been euthyroid on the newborn screen, developed unexplained hospital-acquired hyponatremia (serum Na 124 mEq/L) while on full oral feeds. He was euvolemic, appeared well and was without myxedema. An evaluation of hyponatremia was negative with the exception of severe primary hypothyroidism (TSH 315.4 IU/mL, repeat 540 IU/mL). The hyponatremia resolved with thyroxine supplementation. This case demonstrates that severe hypothyroidism can result in hyponatremia in infants. It is critical to consider hypothyroidism in the evaluation of an infant with unexplained hyponatremia as untreated hypothyroidism can lead to profound developmental delays.